PENGETAHUAN DENGAN KESEDIAN VAKSINASI COVID-19 BOOSTER 1 PADA MAHASISWA PRODI SARJANA ADMINISTRASI KESEHATAN STIKES AL-SU’AIBAH PALEMBANG - RIANA DEWI RIANA; Deska Herliani; Ferry Adhinata; Zulaikha Agustinawati; Lidya Fransisca (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2023)
Background: Covid-19 booster vaccination is vaccination after a person has received a complete dose of primary vaccine (doses 1 and 2), booster doses are vaccine doses that help increase protection from two doses of Covid-19 vaccine at the beginning, booster vaccines will provide longer protection against corona virus. The aim of this study was to determine the relationship between Knowledge and Willingness to Vaccinate Covid-19 Booster 1 in Undergraduate Health Administration Study Program Students, STIKES Al-Su'aibah Palembang. Methods: The research design was cross sectional with a quantitative research design. All students of the Bachelor of Health Administration Study Program, STIKES Al-Su'aibah Palembang were included in this study. Results: Based on the findings of this study, there is a significant relationship (p value = 0.000) between knowledge and willingness to vaccinate Covid 19 Booster 1 in Undergraduate Students of Health Administration STIKES Al-Su'aibah Palembang in 2023. Conclusion: The higher the knowledge mastered, the more as well as broad knowledge regarding the actions that need to be taken, as well as understanding the benefits of implementing the vaccination program itself to reduce the spread of COVID-19.